2008
DOI: 10.3171/ped/2008/1/4/305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MAGE and GAGE genes in medulloblastoma and modulation of resistance to chemotherapy

Abstract: Object Cancer testis antigens (CTAs) were initially identified by their ability to elicit autologous T-cell–mediated immune responses in patients with melanoma. The CTA genes are widely expressed in a variety of human cancers, such as melanoma, breast cancer, lung cancer, esophageal cancer, and hepatocellular carcinoma; however, their expression in pediatric brain tumors, such as medulloblastoma (MB), has not been the subject of in-depth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…A recent study investigating the influence of cancer/testis antigens on t-cell-mediated immune response in patients suffering from medulloblastoma also found an impact of MAge-A expression level on the response to chemotherapeutic drugs cisplatin and etoposide (16). these findings are relevant to oral squamous cell carcinoma, since cisplatin is one of the pillars of anti-neoplastic treatment of this tumour.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study investigating the influence of cancer/testis antigens on t-cell-mediated immune response in patients suffering from medulloblastoma also found an impact of MAge-A expression level on the response to chemotherapeutic drugs cisplatin and etoposide (16). these findings are relevant to oral squamous cell carcinoma, since cisplatin is one of the pillars of anti-neoplastic treatment of this tumour.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that the paclitaxel-sensitive human ovarian cancer cell line OVCAR8 overexpresses MAGE2 and MAGE6, which leads to enhanced resistance of these cells to paclitaxel and doxorubicin but not other drugs, such as topotecan and cisplatin (5). Furthermore, the inhibition of MAGE-A and GAGE expression was shown to increase apoptosis in medulloblastoma cells and to sensitize these cells to cisplatin and etoposide (6). Similarly, the downregulation of CAGE in the drugresistant human melanoma cell line Malme3M and the human hepatic cancer cell line SWU387 was found to increase drug sensitivity resulting from apoptosis induction (7).…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing PAGE4 Attenuates Cell Survival-Up-regulation of several CTAs including PAGE4 is associated with drug resistance in cancer cells (41)(42)(43)(44). Given the intrinsic nature of IDPs to engage in promiscuous interactions and the presence of a putative DNA-binding region in PAGE4, we hypothesized that PAGE4 may play a critical role in cancer cells by mitigating the genotoxic stress caused by cytotoxic drugs either by interacting with key proteins or by directly binding DNA (or both).…”
Section: Page4 Contains a Nls And Is A Putative Dna-binding Protein-tmentioning
confidence: 99%